Integrating Folk Values into Primary Education in Bangladesh: A Sustainability Perspective - Tasnim, Saria (Curtin University, 2024)
Comprising of five refereed publications, this thesis examines the potential of using folklore in primary education in Bangladesh to strengthen the development of sustainability values. Aimed at different aspects of education for sustainability, the publications employ curriculum and desktop analysis, interviews and a survey of teachers combined with content analysis. The thesis introduces the concept, content and context (3C) approach to incorporate story-telling and contributes to reviving the folkloric sustainability values as an educational tool.